PELATIHAN TEKNIS CANVA FOR EDUCATION UNTUK MENGEMBANGKAN MEDIA PEMBELAJARAN INTERAKTIF SDN DI DESA KLATAKAN - Hasanah, Nur; Ambarsari, Ida Fitriana; Muhafizah, Siti; Muawanah, Kholisatul; Sufyan, Ahmad (STKIP PGRI SITUBONDO, 2024)
The activity was carried out to provide training on the use of Canva as a learning medium to develop interactive learning media for SDN in Klatakan Village through the application of Canva for education. Through technical guidance to teachers and technology integration, it is hoped that this can increase student participation and improve learning outcomes. The use of information and communication technology is very important in delivering material, especially visualization. Presentation media like this can be used to explain material. The training was carried out in the first stage, namely conducting a field survey, providing Canva training materials, practicing creating learning media using Canva and providing a satisfaction questionnaire with the technical training using a questionnaire as a method or way of evaluating. By asking questions via Google from ranging from levels of satisfaction, dissatisfaction, quite satisfaction, very satisfaction. Based on the statistics above, the percentage level of participant satisfaction approaches 65% very satisfied, 10% quite satisfied, 35% satisfied from the total.